2020
DOI: 10.1002/cne.24909
|View full text |Cite
|
Sign up to set email alerts
|

Majority of cerebrospinal fluid‐contacting neurons in the spinal cord of C57Bl/6N mice is present in ectopic position unlike in other studied experimental mice strains and mammalian species

Abstract: Cerebrospinal fluid contacting neurons (CSF‐cNs) represent a specific class of neurons located in close vicinity of brain ventricles and central canal. In contrast with knowledge gained from other vertebrate species, we found that vast majority of CSF‐cNs in the spinal cord of C57Bl/6N mice is located in ectopic distal ventral position. However, we found that small number of ectopic CSF‐cNs is present also in spinal cord of other investigated experimental mice strains (C57Bl/6J, Balb/C) and mammalian species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 75 publications
3
36
1
Order By: Relevance
“…A recent study suggested that ventral PKD2L1 + cells might be the result of ectopic distribution that depends on the animal models or strains tested (Tonelli Gombalová et al, 2020). In agreement with our study, the authors reported the presence of distal PKD2L1 expressing neurons in several animal models as well as in the C57Bl6/J (the mouse line used in our study).…”
Section: Which Cellular Origin and Lineage For Dpkd2l1 Neurons?supporting
confidence: 93%
See 2 more Smart Citations
“…A recent study suggested that ventral PKD2L1 + cells might be the result of ectopic distribution that depends on the animal models or strains tested (Tonelli Gombalová et al, 2020). In agreement with our study, the authors reported the presence of distal PKD2L1 expressing neurons in several animal models as well as in the C57Bl6/J (the mouse line used in our study).…”
Section: Which Cellular Origin and Lineage For Dpkd2l1 Neurons?supporting
confidence: 93%
“…
pathological dysfunction. Finally, although CSF-cN neurogenesis has been shown to occur only during development they have been shown to retain an incomplete maturity state (Stoeckel et al, 2003;Sabourin et al, 2009;Orts-Del'Immagine et al, 2014 and might be reactivated and take part to plasticity and regenerative processes associated with the ependymal stem cell niche.Most studies focused on ependymal and sub-ependymal PKD2L1 + CSF-cNs (located at less than 50 µm from the CC) however previous observations (Orts-Del'immagine et al, 2012;Djenoune et al, 2014;Orts-Del'Immagine et al, 2014), recently confirmed (Tonelli Gombalová et al, 2020), mentioned the presence of PKD2L1 + cells located more distally from the CC. The developmental origin for these distal PKD2L1 + cells is still unclear but as ependymal cells located along the ventral midline in regions distal from the CC display specific electrophysiological properties of neuronal progenitor (eg.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that CSF-cNs maintain a relatively primitive cell phenotype and show a strong potential as NSCs during in vitro culture. Petracca and Colleagues showed that CSF-cNs were negative for GFAP in animal tissues, a marker both for astrocyte and neural stem cell (Petracca et al, 2016;Tonelli Gombalova et al, 2020). But in our research, GFAP was expressed in primary culture of CSF-cNs and neurospheres formed by CSF-cNs in cell culture.…”
Section: Discussioncontrasting
confidence: 66%
“…There is no clear connection between CSF-cNs and the glyt2+ cells reported here. While CSF-cNs can be found ectopically (outside of the ependymal layer surrounding the central canal; [17,6]), they are known to be GABAergic across vertebrates [3]. Further, a recent transcriptome analysis of spinal dynophin-lineage cells found a cluster with characteristics of CSF-cNs but comparatively low expression of glyt2 transcript (SLC6A5; Fig.…”
Section: Discussionmentioning
confidence: 99%